Sifat Fisikokimia Biji Kopi Robusta Solok Radjo dengan Lama Penyangraian Berbeda - Heraldy Armanda Hutahaean; Farida Hanum Hamzah; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The roasting is the process of forming the color and aroma of green coffee beans. The coffee roasting process not only changes the physical appearance of the coffee beans but also rearranges the chemical makeup. This study aims to obtain the best roasting time on the physicochemical properties of Robusta Solok Radjo coffee beans based on SNI 01-3542-2004. The research design used was a completely randomized design (RAL) non factorial with roasting time treatment consisting of roasting time consisting of 8 minutes, 10 minutes, 12 minutes, 14 minutes, and 16 minutes. The results showed that the duration of roasting had a significant effect on moisture content, ash content, degree of acidity, and caffeine content in roasted coffee beans. The best treatment in this study was L1 treatment with a roasting time of 8 minutes. The L1 treatment of roasted coffee beans in this study had an average value of water content of 2.22%, ash content of 3.09%, degree of acidity 5.06, caffeine content 1.56%, color index 27.65%. The hedonic assessment obtained by an average rating of the aroma of roasted coffee beans was 3.87 (like). Parameters of water content, ash content, caffeine content and aroma have met SNI 01-3542-2004. Keywords: robusta coffee, roasting, roasting duration